Big data capabilities, ESG performance and corporate value - Cai, Cen; Li, Yijia; Tu, Yongqian (International review of economics & finance, 2024)
Utilizing panel data from listed companies in China spanning from 2012 to 2022, this study explores the correlation between big data capabilities, ESG (Environmental, Social, and Governance) performance, and enterprise value. The findings reveal that strong big data capabilities contribute to an increase in enterprise value. Additionally, improved ESG performance also leads to an augmentation in enterprise value, while exerting a favorable moderating effect. Furthermore, there exists a disparity in how ESG performance impacts the value of state-owned and non-state-owned enterprises, with a more pronounced effect observed in state-owned enterprises.